Human Trafficking Is a Public Health Issue A Paradigm Expansion in the United States - Chisolm-Straker, Makini; Stoklosa, Hanni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This clear-sighted reference examines the public health dimensions of labor and sex trafficking in the United States, the scope of the crisis, and possibilities for solutions. Its ecological lifespan approach globally traces risk and protective factors associated with this exploitation, laying a roadmap towards its prevention. Diverse experts, including survivors, describe support and care interventions across domains and disciplines, from the law enforcement and judicial sectors to community health systems and NGOs, with a robust model for collaboration. By focusing on the humanity of trafficked persons, a public health paradigm broadens our understanding of and ability to address trafficking while adding critical direction and resources to the criminal justice and human rights structures currently in place. Among the topics covered: Children at Risk: Foster Care and Human Trafficking LGBTQ Youth and Vulnerability to Sex Trafficking Physical Health of Human Trafficking Survivors: Unmet Essentials Research Informing Advocacy: An Anti-Human Trafficking Tool Caring for Survivors Using a Trauma-Informed Care Framework The Media and Human Trafficking: Discussion and Critique of the Dominant Narrative Human Trafficking Is a Public Health Issue is a sobering read; a powerful call to action for public health professionals, including social workers and health care practitioners providing direct services, as well as the larger anti-trafficking community of advocates, prosecutors, taskforce members, law enforcement agents, officers, funders, and administrators. (3z(BAn extraordinary collection of knowledge by survivors, academics, clinicians, and advocates who are experts on human trafficking. Human Trafficking is a Public Health Issue is a comprehensive offering in educating readers on human trafficking through a multi-pronged public health lens.(3y (BMargeaux Gray: Survivor, Advocate, Artist, Public Speaker.s
Introduction to Human Trafficking: Who Is Affected -- Trafficked and Missed -- Trafficked and Survived -- Sex Trafficking in the US.-The Ignored Exploitation: Labor Trafficking in the US -- Trafficking of US Domestic Minors -- Children at Risk: Foster Care and Trafficking -- Sex Trafficking in Indian Country.-LGBT and Trafficked.-Mental Health of Survivors: Diagnoses and Necessities -- Physical Health of Survivors: Unmet Essentials.-Substance Abuse and the Life -- The Development and Psychology of Young Minds: Communities Can Prevent Exploitation -- Legal Support for Trafficked Minors: Improving the Health of Young Survivors -- NGOs and the Anti-Trafficking Movement: Advocacy and Service -- Faith-Based Organizations and Anti-Trafficking Efforts -- Research as an Anti-Trafficking Effort -- Trauma-Informed Care in Anti-Trafficking Work.-Law Enforcement Agents as Advocates: Traditional Policing and the Shift to Survivor-Centered Service -- Community Health Clinics and Direct Care Provision -- Trafficking in the Media: Which and Whose Stories Get Told and Why -- Education of Youth and Communities: Prevention Efforts -- From Not-for-Profit Work to Federal Interventions: The Mainstreaming of Human Trafficking.-Moving Forward: Next Steps in Prevention and Intervention.
Keywords: Medicine; Emergency medicine; Public health; Social justice; Human rights; Medicine & Public Health; Public health; Social Justice, Equality and Human Rights; Emergency medicine